The Effects of Landscape Urbanization on the Gut Microbiome: An Exploration Into the Gut of Urban and Rural White-Crowned Sparrows - Phillips, Jennifer N.; Berlow, Mae; Derryberry, Elizabeth P. (Frontiers in Ecology and Evolution, 2018)
Urban habitats present new ecological and evolutionary challenges for animals. Noise and infrastructure often change behavior and community composition, with potential physical costs such as decreased condition. However, the underlying mechanisms driving these patterns are virtually unknown. One potential driver of condition within a species is the diversity of the gut microbiome. Here, we investigate how the urban habitat affects the gut microbiome of White-crowned Sparrows (Zonotrichia leucophrys) using spatial analyses of land cover (impervious, scrub, grass, and trees) at the regional level and territory level in urban San Francisco, CA and nearby rural Point Reyes, CA. We hypothesized that urbanization of habitats affects gut microbial composition and diversity through direct effects on diet and/or indirect environmental effects. We measured gut microbial community diversity from 16s rRNA sequences amplified from cloacal swabs. We find that the urban and rural microbiomes are significantly different, such that the urban microbiome is more diverse than the rural microbiome. This relationship may be due to a more variable landscape in urban habitats as compared to rural habitats, which are mainly composed of native scrub. We do not find support for regional impervious cover affecting the gut microbiome, but the more precise territory level analyses show that higher tree cover correlates with increased alpha diversity and impervious cover correlates with relative abundances of gut microbial taxa (Unifrac beta diversity). Although some studies show that gut diversity affects physiology, our measures of body condition do not indicate a strong relationship. Our results highlight how changes in the landscape may affect the gut microbiome of animals in an ever-urbanizing world, and provides a baseline for future studies of how anthropogenic change affects communities at multiple levels.